Slideshare uses cookies to improve functionality and performance, and to provide you with relevant advertising. If you continue browsing the site, you agree to the use of cookies on this website. See our User Agreement and Privacy Policy.

Slideshare uses cookies to improve functionality and performance, and to provide you with relevant advertising. If you continue browsing the site, you agree to the use of cookies on this website. See our Privacy Policy and User Agreement for details.

Like this presentation? Why not share!

6,128 views

5,300 views

5,300 views

Published on

No Downloads

Total views

6,128

On SlideShare

0

From Embeds

0

Number of Embeds

13

Shares

0

Downloads

189

Comments

0

Likes

4

No embeds

No notes for slide

- 1. Pythagorean Theorem T- 1-855-694-8886 Email- info@iTutor.com By iTutor.com
- 2. Pythagoras theorem The Pythagorean theorem is related to the study of sides of a right angled triangle. It is also called as Pythagoras theorem. The Pythagorean theorem states that, In a right triangle (length of the hypotenuse)2 = {(1st side)2 + (2nd side)2} a b cc2 = a2 + b2
- 3. In a right angled triangle three sides: Hypotenuse, Perpendicular and Base. The base and the perpendicular make an angle is 900.So, according to Pythagorean theorem: Pythagoras theorem (Hypotenuse)2 = (Perpendicular)2 + (Base)2 Pythagoras Theorem Proof: p b h A B C Given: Δ ABC is a right angled triangle where <B = 900 And AB = P, BC= b and AC = h To Prove: h2 = p2 + b2
- 4. Construction : Put a perpendicular BD from B to AC , where AD = x and CB = h-x , p b h A B C D x (h-x) Proof : Consider the two triangles Δ ABC and Δ ABD, these two triangles are similar to each other because of AA similarity. This is because both the triangle have a right angle and one common angle at A. In Δ ABC and Δ BDC both are similar So by these similarity, = = p h x p b h (h-x) b AND Pythagoras theorem
- 5. = = p h x p b h (h-x) b AND P2 = h * x and b2 = h (h – x) Adding both L.H.S. and R.H. S. P2 + b2 = h.x + h (h - x) Or P2 + b2 = h.x + h2 – h.x h2 = p2 + b2 Pythagoras theorem p b h A B C D x (h-x)
- 6. converse of the Pythagoras Theorem In a triangle, if square of one side is equal to the sum of the squares of the other two sides, then the angle opposite the first side is a right angle. A B C Given: In a triangle ABC in which AC2 = AB2 + BC2 To prove: ∠ B = 90
- 7. Construction: A Δ PQR right angled at Q such that PQ = AB and QR = BC (figure) Proof: from Δ PQR, we have: PR2 = PQ2 + QR2 (Pythagoras Theorem, as ∠ Q = 90 ) or, PR2 = AB2 + BC2 (By construction) ……………. (i) converse of the Pythagoras Theorem P Q R A B C
- 8. But given, AC2 = AB2 + BC2……………………. (ii) From (i) and (ii) AC = PR …………………………….(iii) Now, in Δ ABC and Δ PQR, AB = PQ …………………(By construction) BC = QR ………………...(By construction) AC = PR …………….Proved in (iii) above P Q R A B C converse of the Pythagoras Theorem
- 9. So, Δ ABC ≅ Δ PQR …………….(SSS congruence) Therefore, ∠ B = ∠ Q ...........................(CPCT) But, ∠ Q = 90 …………………..(By construction) So, ∠ B = 90 Proved P Q R A B C converse of the Pythagoras Theorem
- 10. The End Call us for more information: www.iTutor.com 1-855-694-8886 Visit

No public clipboards found for this slide

×
### Save the most important slides with Clipping

Clipping is a handy way to collect and organize the most important slides from a presentation. You can keep your great finds in clipboards organized around topics.

Be the first to comment